Variation in soil organic carbon within highland grasslands of Langtang National Park, Nepal - Shrestha, Keshab (International Journal of Environment, 2016)
Grassland also plays important role in food security. The estimated grassland area in Nepal is about 1.75 million ha. Most of the grassland in Nepal is located in higher elevation above, 2000 meter. The aim of this research is to observe difference in SOC of grassland in different altitude. Soil samples were collected from grasslands of altitude: 1500- 2000m, 2001- 2500m, 2501-3000m, 3001- 3500m and 3501- 4000m. The soil samples were collected at successive depths in each grassland i.e. 0 – 10 cm, 10 – 20 cm and 20 – 30 cm. The maximum SOC was found in grassland at altitude 3001 m- 3500m. The lowest was SOC was found in grassland at altitude 3051m – 4000m. Correlation analysis between altitude and SOC shows that SOC is positively correlated with altitude with correlation coefficient 0.850 (significant at P